"Te:mos o serra cura::do, temos o ni:sa, temos o serpa do:p." Suggesting products to buy, shaping materiality and multisensoriality in shop encounters - Mondada, Lorenza (Calidoscópio, 2021)
Adopting the perspective of multimodal conversation analysis, the paper shows the methodic organization of an action, making suggestions, achieved by sellers in response to customers’ requests for recommendations in shop encounters, and involving the showing and listing of available products. This focus on a specific sequential environment and institutional ecology, enables an exemplary discussion of how this action is multimodally formatted, embedded in its context, and shaped in relation to objects as discursive referents as well as materialities to be pointed at, looked at, touched and sensed in multiple ways. More generally, this focus enables to address two sets of issues: on the one hand, it elucidates the nexus between action, institutionality and materiality, including the role of multisensoriality in engaging with the qualities of buyable objects. On the other hand, it addresses the nexus between action and referential practices for introducing and presenting new referents, within an interactional perspective locating these grammatical practices and their systematic features within their praxeological context. On the basis of video data recorded in a gourmet shop in Lisbon, Portugal, this double focus targets issues of sensoriality and socialization in food culture, as well as issues of grammar in interaction, casting some light on situated uses of the verb ter for introducing new referents. Keywords: Social Interaction; Shop Encounters; Multimodality and Multisensoriality.